Choosing to Love - Hinsdale, Mary Jo (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
This essay proposes a pedagogical ethic of love based on the four brahma-viharas -- also called the divine abodes-- of Theravada Buddhism. Witnessing, Kelly Oliver’s theory of mutual subjectivity, finds practical expression in the brahma-viharas, a comprehensive way to train the mind and heart to sustain an ethic of love in all of our relationships. Together, witnessing and the brahma-viharas offer an approach whereby we may choose to love students and to cultivate more open, responsive and egalitarian relations with them, in spite of academic asymmetries of power. In perplexing or vexing interactions with students, I draw strength from three of the four divine abodes: metta (lovingkindness), karuna (compassion), and upekkha (equanimity). Consistently applying the contemplative practices associated with these states begins to disentangle the threads of complicated social relations.